Integration of workplace readiness skills into tourism educational curriculum for graduates employability - Nurhazani Mohd Shariff (Tanjong Malim, 2021)
Integration of workplace readiness skills into tourism educational curriculum for graduates employability by Nurhazani Mohd Shariff